On the closure of one point sets in T0-spaces - Dovgoshey, Oleksiy; Shanin, Ruslan (Elsevier BV, 2026)
Let X be a set and 2X be a set of all subsets of X. The necessary and sufficient conditions under which a mapping X → 2X is a closure of one-point sets in some T0-space (X, τ) are described. It is proved that every T0-Alexandroff space is quasimetrizable by some equidistant quasi-metrics.